2002
DOI: 10.21273/jashs.127.6.931
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability Analysis of Yield Components in Cucumber

Abstract: Three U.S.-adapted Cucumis sativus var. sativus L. lines and one C. sativus var. hardwickii (R.) Alef.-derived line were crossed in a half-diallel design to determine their combining ability for several yield-related traits (yield components). Six F1 progenies were evaluated in a randomized complete block design with eight replications in 1999 and 2000 for fruit number and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The relatively small deviation of predictability factor from unity observed in this study indicates the importance of additive gene action for the genetic control of number of fruits per plant suggesting that cyclic selection should be effective for improving number of fruits per plant. Lopez-Sese and Staub (2002) reported that fruit number was under the genetic control of both additive and dominant gene actions. Sarkar and Sirohi (2011) also reported the overdominant gene action for the genetic control of fruit number per plant and suggested heterosis breeding for achieving higher yields in cucumber.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively small deviation of predictability factor from unity observed in this study indicates the importance of additive gene action for the genetic control of number of fruits per plant suggesting that cyclic selection should be effective for improving number of fruits per plant. Lopez-Sese and Staub (2002) reported that fruit number was under the genetic control of both additive and dominant gene actions. Sarkar and Sirohi (2011) also reported the overdominant gene action for the genetic control of fruit number per plant and suggested heterosis breeding for achieving higher yields in cucumber.…”
Section: Discussionmentioning
confidence: 99%
“…Improving fruit yield requires adequate information regarding the nature of GCA and SCA available in a wide array of genetic materials to be used in hybridization programmes. Several authors have used different genetic analyses to study combining ability in cucumber for fruit yield and yield components (Lopez-Sese and Staub, 2002;Xing Fang et al, 2004;Munshi et al, 2006;Mule et al, 2011;Sarkar and Sirohi, 2011;Singh et al, 2011;Olfati et al, 2012;Ene et al, 2018) and gynoecious sex expression (Wahid et al, 2003;Staub et al, 2005;Dey et al, 2010;Singh et al, 2011;Pati et al, 2015). Combining ability studies have been conducted by Adel and Ali (2013) Golabadi et al (2015) and Ene et al (2018), but these authors used elite parental lines to make crosses.…”
Section: Introductionmentioning
confidence: 99%
“…Golabadi et al [2015] reported the predominant role of additive gene action for the genetic control of fruit number per picking, which agrees well with the present results. Previous studies reported the significance of both additive and dominant gene actions for the genetic control of fruit number per picking [Kanobdee et al 1990, Lopez-Sese andStaub 2002]. Sarkar and Sirohi [2011] also reported the over-dominance of gene action for the genetic control of fruit number per plant.…”
Section: Fruit Number Per Pickingmentioning
confidence: 99%
“…Different genetic analyses have been conducted to study the combining ability in cucumber for fruit yield and its components [Munshi et al 2006, Mule et al 2011, Sarkar and Sirohi 2011, Singh et al 2011, Golabadi et al 2015 using such different genetic designs as diallel and NCD. Studies have been conducted on some economically important traits of cucumber including fruit yield and its components [Lopez-Sese et al 2002, Dogra and Kanwar 2011, Jagesh et al 2013, Golabadi et al 2015. Gulam-ud-Din et al [2002] evaluated the combining ability of 12 different traits in cucumber by line × tester analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Combining ability estimation has always been an important content in plant breeding, which provides a valuable reference for the breeding of inbreds and hybrids (Lv et al, 2012 ). There are some studies on combining ability estimation in cucumber breeding (López-Sesé and Staub, 2002 ; Golabadi et al, 2015 ; Ene et al, 2019 ), where rigorous field experimental design and phenotypic variance decomposition were used to estimate GCA and SCA. In these studies, SCA has a substantial contribution to some traits.…”
Section: Discussionmentioning
confidence: 99%